Innovation networks in biotechnology : actors, relations and strategies - Sousa, Cristina (2012)
The paper addresses innovation networks in a science-based sector, focusing on networks for scientific and technological knowledge access. It investigates the strategic choices made by new biotechnology firms regarding the type of actors and relations that prevail in accessing those networks. The results contribute to on-going debates in the area of innovation networks and knowledge management, both at the methodological and empirical levels. We develop a methodology to investigate the networking behaviour of sciencebased entrepreneurs in their search for scientific and technological knowledge for innovation. We apply it to the case of biotechnology entrepreneurs in a country that is peripheral to the major concentrations of biotechnology knowledge and business, which enables us to gain some insights on the strategies adopted by new entrepreneurial firms to access critical resources in these particular contexts.